2006
DOI: 10.11646/zootaxa.1154.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Coccinellidae (Coleoptera) of the Maritime Provinces of Canada: new records, biogeographic notes, and conservation concerns

Abstract: New records of Coccinellidae in the Maritime Provinces of Canada are reported. The known fauna of the region consists of 47 species: 41 in Nova Scotia, 39 in New Brunswick, and 21 in Prince Edward Island. Of these, records are provided for 13 species newly recorded from Nova Scotia and 14 from Prince Edward Island. Two species, Diomus amabilis (LeConte) and Naemia seriata seriata Melsheimer, are newly recorded in Canada. Didion punctatum (Melsheimer) is removed from the fauna of PEI, and Coccidula lepida LeCon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Microsporidia-infected larvae take longer to develop and cannibalism of infected larvae by uninfected ones may facilitate horizontal transmission of the microsporidium. The coccinellid species that were studied here overlap in their distributions and habitats in North America (Boiteau et al, 1999;Cormier et al, 2000;Gordon, 1985;LaMana and Miller, 1996;Majka and McCorquodale, 2006;Yasuda et al, 2004), and IGP among these species have been observed and studied (Kajita et al, 2000(Kajita et al, , 2006Yasuda et al, 2004). Distribution overlap provides an opportunity for the microsporidium from H. convergens to expand its distribution and host range once infected H. convergens are released.…”
Section: Discussionmentioning
confidence: 88%
“…Microsporidia-infected larvae take longer to develop and cannibalism of infected larvae by uninfected ones may facilitate horizontal transmission of the microsporidium. The coccinellid species that were studied here overlap in their distributions and habitats in North America (Boiteau et al, 1999;Cormier et al, 2000;Gordon, 1985;LaMana and Miller, 1996;Majka and McCorquodale, 2006;Yasuda et al, 2004), and IGP among these species have been observed and studied (Kajita et al, 2000(Kajita et al, , 2006Yasuda et al, 2004). Distribution overlap provides an opportunity for the microsporidium from H. convergens to expand its distribution and host range once infected H. convergens are released.…”
Section: Discussionmentioning
confidence: 88%
“…For example, H. convergens is rarely found in Nova Scotia, with the Wrst and only specimen collected in Halifax in 2001 (Majka and McCorquodale, 2006). However, H. convergens are commercially available for aphid control, and under laboratory conditions, the microsporidium in H. convergens has been transmitted successfully to three coccinellids of Nova Scotia: Coccinella septempunctata (seven-spotted lady beetle), C. trifasciata perplexa (three-banded lady beetle), and Harmonia axyridis (multicolored Asian lady beetle) (Saito and Bjørnson, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Harmonia axyridis continued to be found in further states, and was recently recorded for the first time in Montana (2006) (Foley et al 2009) and Arizona (2008) (Fothergill et al 2010), leaving Wyoming and Alaska as the only states without a record of the species. Harmonia axyridis became established in Canada by 1994 (Coderre et al 1995) and quickly spread across much of the southern part of the country (Majka and McCorquodale 2006). Having recently been recorded in Newfoundland (2009, although an earlier specimen from 2000 was also noted) (Hicks et al 2010), the species has now been found in all but two jurisdictions (i.e.…”
Section: North Americamentioning
confidence: 99%